Mobile apps application to improve safety and health knowledge, attitude and practice among university students - Syed Ismail, Sharifah Norkhadijah; Rangga, Josfirin Uding; Rasdi, Irniza; Abdul Rahman, Umi Raihana; Abu Samah, Mohd Armi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: The application of M-learning or mobile application (app) as a tool to disseminate occupational safety and health (OSH) information among students and staff in the university, to replace the use of conventional notice-board was assessed in this study. Materials and Methods: Study was conducted between February to March 2016 and involved 124 respondents from health sciences program in Universiti Putra Malaysia. OSH information was incorporated into a mobile-app using online software and respondents were requested to use the app for fourteen days. A self-administered questionnaire was used to assess the level of knowledge, attitude and practice of respondents before and after using the app. Results: The mobile app has significantly increased the knowledge score among respondents (z = -7.331, p<0.001). The mean (SD) of knowledge score has increased from 24.39 (5.84) to 30.40 (4.97). The attitude score also has significantly increased from 12.85 (2.04) to 14.02 (2.42) (z= -4.587, p<0.001). The mobile app was not significantly changed the practice (z= -0.688, p=0.491) and the perception among respondents (z= -0.337, p=0.736). Respondents stated that the app was user-friendly (49.4%, N=61), easy to access (N= 64, 51.6%), and have interesting contents (N= 63, 50.8%). They believed continuous used of the app may improve their knowledge (N= 64, 51.6%), and increase their awareness (N= 67, 54.0%) on safety and health. Conclusion: The M-learning (mobile app) has a potential to be used to promote the safety and health culture among students on the campus.